The right amount of trust - Jeffrey Butler; Paola Giuliano; Luigi Guiso (Fondazione Eni Enrico Mattei (FEEM), 2010)
We investigate the relationship between individual trust and individual economic performance. We find that individual income is hump-shaped in a measure of intensity of trust beliefs. Heterogeneity of trust beliefs in the population, coupled with the tendency of individuals to extrapolate beliefs about others from their own levels of trustworthiness, could generate this non-monotonic relationship: highly trustworthy individuals tend to form overly optimistic beliefs, to assume too much social risk and to be cheated more often, ultimately performing less well than those with a belief close to the mean trustworthiness of the population. On the other hand, less trustworthy individuals form overly pessimistic beliefs and avoid being cheated, but give up profitable opportunities, therefore underperforming. The cost of either too much or too little trust is comparable to the income lost by foregoing college. Our findings in large-scale survey data are supported and extended with experimental findings. We show that in the trust game, own trustworthiness and beliefs about others' trustworthiness are strongly correlated and persistent and that patterns in earnings lost due to incorrect beliefs are comparable to those in the survey data.
Keywords: A1; A12; D1; O15; Z1; 330; Trust; Trustworthiness; Economic Performance; Culture; False Consensus